Bromatological chemical study of the fruit of the níspero de palo (Mespilus germanica l.) from Ayacucho - Vargas R., Yanet (2009)
We did the chemical bromatological determination of Mespilus germánca L. (Nispero de palo) from Vilcashuaman province, Ayacucho region - Peru. The evaluation had the following results expressed in grams per 100 g of fresh sample; 73,13 of water; 0,57 for total protein; 0,41 of ether extract; 23.04 of carbohydrates, 0.63 of ash ; 2.22 of raw fiber; 3,82 of reducing sugars; total reducing sugars 12,06. Minerals, expressed in mg per 100g fresh sample: 76,1of sodium, 266, 25 of potassium; 24, 03 of magnesium; 92, 42 of calcium; 28, 48 of phosphorus; 2.02 of iron; 0.76 of zinc; 2, 85 of copper. Also, 14.06 milligrams of vitamin C per 100 g of fresh sample.